Anaerobic pre-treatment of agro-industrial wastes in Kansas: biogas, economic and environmental potential - Weil, Robert C. (Kansas State University, 2019)
Currently in the US, agro-industrial wastes are, for the most part, treated and disposed of off-site at municipal treatment plants and landfills, imposing a burden on municipalities and the environment. Anaerobic pre-treatment of these wastes has long been known to be an effective and environmentally sustainable biotechnology, as biogas is generated in the process and the volume of biosolids is significantly reduced in comparison to aerobic treatment. This biotechnology is widely distributed internationally but less so in the US. This thesis sets forth relevant principles of the biotechnology, evaluates some cases where it is currently adopted in the US, and provides conceptual reactor designs for two case studies. In both cases, biogas yield, solids reduction and organic loading reduction were found to be significant, but economic returns were modest. For the first case study, a meat packing plant, wastewater flow and characteristics data were obtained and analyzed, and an upflow anaerobic sludge blanket reactor design was prepared. For the second case study, a dairy ranch, reactor design results were compared with AgSTAR spreadsheet models available from the USEPA. In order to evaluate the potential to implement this biotechnology throughout agro-industry in Kansas, data was independently gathered, using specific protocols to ensure accuracy and relevance, which allowed the statewide median flow and organic loading parameters from agro-industry to be estimated. A model was developed to estimate biogas potential from flow and TSS, both of which are required NPDES reporting parameters. The estimated biogas yield for the two case studies was consistent with model results. The model results indicate that, if anaerobic wastewater pre-treatment were fully adopted in Kansas agro-industry, a median estimate of 19,800 MMBtu of biogas (methane) could be generated, equivalent to the natural gas demand of about 500 homes. The quantity of biosolids diverted from publicly owned treatment works would be 1,000 – 1,200 tonnes/year. The median BOD5 received from agro-industrial users would be reduced from 1,500 to 420 mg/L. However, a survey of industrial pre-treatment coordinators at agencies receiving agro-industrial wastewater found somewhat unfavorable attitudes towards using anaerobic wastewater pre-treatment. Recommendations for future research and engagement activities are provided.
Keywords: Anaerobic wastewater treatment; Industrial pre-treatment; Regional biogas potential; Kansas agro-industry; Attitudes towards anaerobic biotechnology; Organic loading reduction